Antarctic intermediate water circulation in the South Atlantic over the past 25, 000 years. (5th October 2016) - Howe, Jacob N. W.; Piotrowski, Alexander M.; Oppo, Delia W.; Huang, Kuo‐Fang; Mulitza, Stefan; Chiessi, Cristiano M.; Blusztajn, Jurek
Abstract: Antarctic Intermediate Water is an essential limb of the Atlantic meridional overturning circulation that redistributes heat and nutrients within the Atlantic Ocean. Existing reconstructions have yielded conflicting results on the history of Antarctic Intermediate Water penetration into the Atlantic across the most recent glacial termination. In this study we present leachate, foraminiferal, and detrital neodymium isotope data from three intermediate‐depth cores collected from the southern Brazil margin in the South Atlantic covering the past 25 kyr. These results reveal that strong chemical leaching following decarbonation does not extract past seawater neodymium composition in this location. The new foraminiferal records reveal no changes in seawater Nd isotopes during abrupt Northern Hemisphere cold events at these sites. We therefore conclude that there is no evidence for greater incursion of Antarctic Intermediate Water into the South Atlantic during either the Younger Dryas or Heinrich Stadial 1. We do, however, observe more radiogenic Nd isotope values in the intermediate‐depth South Atlantic during the mid‐Holocene. This radiogenic excursion coincides with evidence for a southward shift in the Southern Hemisphere westerlies that may have resulted in a greater entrainment of radiogenic Pacific‐sourced water during intermediate water production in the Atlantic sector of the Southern Ocean. Our intermediate‐depth records show similar values to a deglacial foraminiferal Nd isotope record from the deep South Atlantic during the Younger Dryas but are clearly distinct during the Last Glacial Maximum and Heinrich Stadial 1, demonstrating that the South Atlantic remained chemically stratified during Heinrich Stadial 1. Key Points: Foraminifera successfully preserve seawater neodymium isotopic composition in the intermediate‐depth South Atlantic There is no evidence for changes in the proportion of Antarctic Intermediate Water in the South Atlantic across the deglaciation More radiogenic neodymium isotopic values indicate that there was a shift in Antarctic Intermediate Water production during the mid‐Holocene